Perilaku Tentang Cuci Tangan Pakai Sabun Di Madrasah Ibtidaiyah Taswirul Afkar - Dewa Ayu Komang Lisna Trijayanti (Universitas Airlangga, 2019)
Background: School is one of the important institution to implementing health promotion program. The problem that need to be noticed is low awareness to wash hands with running water and soap among students. Purpose: The aim of this research is to describe knowledge, attitudes, practice, facility availability, and the teacher's role to support handwashing with soap (HWS) habit among students at Madrasah Ibtidaiyah (MI) Taswirul Afkar Surabaya.Methods: This study used observational descriptive method. The population were students in 4th until 6th grade. Results: Results of the study showed that the majority of students (49.1%) had good knowledge. Regarding the attitudes, the majority of students  (66.7%) had positive attitudes and most of them (78.4%) had good practices on handwashing with soap. The majority of respondents (56.8%) get support from teachers such as counseling. The teachers was not always controlling the facility availability of handwashing (94.1%) and carrying out supervision handwashing with soap practices among students (76.5%). Based on observations, it is found that washbasin is only available in the schoolyard and four bathroom rooms. Conclusion: Student's knowledge, attitude, and Practice about  handwashing with soap in a good category. There is counseling from teachers and there is no control on handwashing facilities.